Individual Insomnia Symptom and Increased Hazard Risk of Cardiocerebral Vascular Diseases: A Meta-Analysis - Hu, Shiyu; Lan, Tao; Wang, Yang; Ren, Lijie (Frontiers in Psychiatry, 2021)
Objective: Previous studies suggested that insomnia was associated with increased risk of cardiocerebral vascular diseases, but not clear in each different insomnia symptom. We performed a meta-analysis to investigate the association of individual insomnia symptoms and risk of cardiocerebral vascular diseases (CVDs). Methods: In this meta-analysis, we systematically searched published articles by using electronic databases including PubMed, Cochrane Library, MedLine and Google scholar. Studies were enrolled if they indicated clear insomnia symptoms, prospective and evaluated the association of insomnia symptoms and cardiocerebral vascular diseases outcome in adults free of cardiocerebral vascular diseases at baseline. Results: There were 7 prospective cohort studies with sample size range from 2960 to 487200 included in this meta-analysis. Mean follow-up duration was 10.6 years. Insomnia symptoms of having difficulty initiating or maintaining sleep (DIS or DMS), nonrestorative sleep (NRS) and early morning awakening (EMA) were analyzed in this study. All studies were compared under a random-effects model, NRS, DIS and DMS was respectively related to 16% (HR 1.16, 95% CI 1.07-1.24), 22% (HR 1.22, 95% CI 1.06-1.40), 14% (HR 1.14, 95% CI 1.02-1.27) higher risk of first ever CVDs incidence during the follow up. Based on our analysis, EMA was not a risk factor of CVDs (HR 1.06, 95% CI 0.99-1.13). Conclusion: This study suggested symptoms of DIS, DIM or NRS was associated with higher risk of CVDs incidence in insomnia patients free of CVDs at baseline. But this association was not significant in insomnia patients complained about EMA.